THE INFLUENCE OF LEADERSHIP AND ORGANIZATIONAL CULTURE ON WORK MOTIVATION AND EMPLOYEE PERFORMANCE PT. BANK RIAU KEPRI, PEKANBARU BRANCH - Mhd Fathurrahman Elka Putra; Sri Indarti; Raden Lestari Ganarsih (LPPM Press STIE Indragiri Rengat, 2021)
The research was conducted at PT Bank Riau Kepri Pekanbaru branch. The aim is to determine the direct effect of leadership and organizational culture on work motivation and employee performance of PT. Bank Riau Kepri Pekanbaru branch. This study took a sample of 130 people. The variables used are leadership, organizational learning, work motivation and employee performance. Data were analyzed using path analysis (path analysis) The results showed that there was an influence of leadership and organizational culture on work motivation. and there is an influence of leadership and organizational culture on performance. And there is an influence of leadership and organizational culture on employee performance with work motivation as an intervening variable. The better the work motivation that is owned by employees, the performance will increase